Preliminary Phytochemical Studies, GC-MS Analysis, and Anti-Nephrototic Activity of Ethanol Extract of Phoenix dactylifera L - Warsinah Warsinah; Eka Prasasti Nur Rachmani; Hartiwi Diastuti (Molekul, 2022)
Date palm seeds (Phoenix dactylifera L.) are known to contain phenolic compounds that have the potential as natural nephroprotective agents. Phenolics with solvents suitable for polarity and compounds identified by phytochemical screening, GC-MS analysis, and activity assays. This research went through 3 stages, screening with exploration and qualitative analysis of GCMS. The anti-nephrotoxic activity test used a pre-posttest controlled group design. In this study, rats have divided into six groups, namely Healthy control, negative control, and three treatment groups with ethanol extract of dates 150, 300, and 600 mg/kg. Mice were induced with 1% carrageenan twice a week. On macroscopic observation, date palm seeds are oval with indentations and light brown with a hard texture. Microscopic profile, endosperm, parenchyma, endocarp, stone cells, collenchyma, starch, oil cells, and carrier bundles. Physicochemical analysis, water content (8%), ash content (1.15%), fiber content (14.96%), and ethanol soluble extract content (10.3%). GC-MS analysis showed phenol,2,6-bis(1,1-dimethyl ethyl)-4-methyl, 1,2-benzene dicarboxylic, and dihydromethyl jasmonate. A dose extract ethanol of 600 mg/kg BW reduces urea and creatinine levels up to 8,3 mg/dl and 0.132 mg/dl. The conclusion of the phytochemical study obtained a pharmacognostic profile. The GCMS analysis obtained the compound. The activity of the ethanol extract of date palm seeds can reduce urea and creatinine levels so that it developed as an anti-nephrotoxic alternative from natural ingredients.